On the Usability of Parallel Coordinates Plots for Representing Behavioral Attributes in LMS Platforms - Silva, Nathan Alves de L.; Dourado, Raphael A.; Rodrigues, Rodrigo L.; Cavalcanti, Aldo A. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2018)
This paper investigates the suitability of using Data Visualization, specifically Parallel Coordinates Plots (PCP), as an instrument for helping distance learning instructors identify students with poor performance. To answer this question, we developed a web application that lets users generate and interact with PCPs and evaluated it with usability tests inspired by the NOVIS framework — a usability framework specifically designed for evaluating data visualizations. The results show that PCPs and Data Visualization are perceived, by distance learning instructors, as an invaluable tool for following student progress on Virtual Learning Environments.